2020
DOI: 10.14393/bj-v36n3a2020-47783
|View full text |Cite
|
Sign up to set email alerts
|

Non-destructive identification of physical damage in mung bean (Vigna radiata L.) seeds by X-ray image analysis

Abstract: Global demand for pulses such as the mung bean has grown in the last years. For successful production of these crops it is necessary to use high quality seeds. Methodologies based on X-ray image analysis have been used as a complementary tool to evaluate the physical quality of seeds due to their speed and potential for automation. The aim of this study was to evaluate the efficiency of X-ray analysis for non-destructive evaluation of the physical quality of Vigna radiata seeds and to relate the variables obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
1
6
0
3
Order By: Relevance
“…In rice seeds, with the lots under study, this parameter showed no correlation with the physiological potential (Figure 5B). Similar results were also observed in mung bean (Vigna radiata L.) seeds by Machado et al (2020), who found that the relative density depends on characteristics of the seed of the studied species, such as oil and carbohydrate contents, thickness, among others.…”
Section: Resultssupporting
confidence: 85%
“…In rice seeds, with the lots under study, this parameter showed no correlation with the physiological potential (Figure 5B). Similar results were also observed in mung bean (Vigna radiata L.) seeds by Machado et al (2020), who found that the relative density depends on characteristics of the seed of the studied species, such as oil and carbohydrate contents, thickness, among others.…”
Section: Resultssupporting
confidence: 85%
“…The germinative behavior of Q. quesneliana can be complemented by the t50, uniformity of germination, mean germination time, and germination speed coefficient (Figure 3). Recently, these and other similar indexes have been often used to assess the vigor of agricultural species such as Brachiaria grass (MEDEIROS et al, 2020a), melon (MEDEIROS et al, 2020b), mung bean (MACHADO et al, 2020), and others. However, although there was no comparison between different lots, they are unexplored in Bromeliads and may bring future contributions to research with these species.…”
Section: Resultsmentioning
confidence: 99%
“…O estudo da morfometria das sementes pode trazer benefícios para programas de melhoramento genético (TANABATA et al, 2012). Informações desse tipo demonstram alta relação com o vigor das plântulas JAVORSKI et al, 2018;MEDEIROS et al, 2020).…”
Section: Resultsunclassified
“…Em sementes de melão (Cucumis melo L.), a análise de raios-X permitiu a observação das estruturas internas e a diferenciação de cultivares. Nessa espécie, a densidade relativa e densidade integrada, que são variáveis relacionadas ao número de pixels na imagem, se destacaram em predizer sobre o potencial fisiológico das sementes, o que demonstra o nicho de variáveis que pode ser retirado dessa análise (MEDEIROS et al, 2020).…”
Section: Resultsunclassified
See 1 more Smart Citation